The Predictive Ability of a Supervisory Style on the Well-Being and Creativity of Employees at the Jordanian Potash Company - Aldames, Wafaa Khaled ahmad; Banat, Suhaila Mahmoud; Albawareed, Khaled Ahmad; Ashour, Lina Mahmoud Arabi; Alwaely, Suad Abdalkareem (Migration Letters, 2023)
The current study aimed to examine the predictive ability of supervision styles for creativity at work and psychological well-being among employees at the Jordanian Potash Company. A survey was conducted using supervision styles, creativity at work, and psychological well-being measures on 200 employees ranging in age from 22 to 55. The study also investigated whether there were differences in this predictive ability based on marital status, age, and years of experience. The results of the study indicated that the most common supervision style was the democratic style. The results also showed a predictive ability of supervision styles for creativity at work, with regression coefficients explaining 9.5% of the variance. The values of standardized regression coefficients were positive and statistically significant for the democratic style, negative and not statistically significant for the authoritarian style, and positive and not statistically significant for the permissive style. Furthermore, the study revealed a predictive ability of supervision styles for psychological well-being, with regression coefficients explaining 18% of the variance. The values of standardized regression coefficients were positive and statistically significant for the democratic style, positive and not statistically significant for the authoritarian style, and statistically indicative for the permissive style. The study found no significant differences in the predictive ability of supervision styles for creativity at work and psychological well-being based on variables such as age, marital status, and years of experience.